Evaluation of facilities performance on students’ satisfaction in Northern Nigerian Universities - Abdullahi, Isa (2017)
Performance evaluation of academic facilities of HEIs is very critical to educational effectiveness. Presently, there is limited or no research/data in Nigeria to assess how extensively the use of or lack of academic facilities benchmarking practices. The aim of this research was to develop a facilities performance framework for HEIs academic facilities in order to serve as a reference model for policy makers while designing HEIs facilities standard targeted towards improving facilities performance for enhanced student satisfaction. Quantitative research approach using survey design was adopted. Data was collected using closed-ended questionnaires distributed to a sample of 1000 student randomly selected from three universities in the northern Nigeria out of which 735 were considered valid for the analysis. Research questions were answered by testing the proposed research hypothesis which were developed for the research. The descriptive analyses were conducted using the Statistical Package for Social Science Software (SPSS version 23) while the inferential statistics were analyzed using a Partial Least Squares Structural Equation Modelling software (SmartPLS version 3.0). Overall, the result found that facilities performance significantly influenced student satisfaction. The R-square value indicated that performance of the HEIs component facilities explained 63 percent of the variance in students’ satisfaction. Furthermore, it was found that 66.7 percent of the performance of HEIs components facilities was explained by the performance of both physical and non-physical facilities that constitutes the HEIs academic facilities. The implication of this results points to the importance of including students’ feedback in the facilities management aspect of HEIs. This is for the fact that students’satisfaction was shown to be significantly related to the condition of the university facilities. It is recommended that future research should focus on identifying students satisfaction with academic facilities in the HEIs using experience as a measure of facilities performance to promote the concept of best practices benchmarking for the institutions to esterblished quality facilities in their institutions.